Identifing the destination image and its attributes: The case of Central and Eastern European cities - Nowacki, Marek; Niezgoda, Agnieszka (Identyfikacja atrybutów wizerunku wybranych miast Europy Środkowo-Wschodniej, 2019)
The aim of the work is to identify the unique attributes of Central and Eastern European cities in the reviews posted on TripAdvisor. These attributes can determine the competitive advantage on the tourism market. The research data were downloaded from the English-language TripAdvisor website [https://www.tripadvisor.co.uk]. The reviews concerning tourist centres of selected cities (“Things to do…” category) were collected. These concerned the areas where tourism is concentrated in the cities: historic centres, old towns or old market squares. The most popular tourism cities in Central and Eastern Europe were selected: Poznan, Wroclaw, Cracow, Warsaw, Prague, Bratislava and Vienna. A total of 28,794 reviews were downloaded. The most common words appearing in the reviews were counted using the text mining procedure. The analysis of frequency revealed 76 unique words. Then the correspondence analysis was performed. Among the examined cities, Bratislava has the largest number of unique attributes (words), and Prague the least. The similarities in terms of image attributes occur in Poznan, Wroclaw and Prague, and in the second group – Warsaw and Bratislava. Vienna and Krakow do not show any similarities towards the other cities
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 118-127
Keywords: TripAdvisor; text mining; attributes; image; cities; atrybuty; wizerunek; miasta